PERLINDUNGAN HUKUM KORBAN KEKERASAN DALAM RUMAH TANGGA PADA PROSES PENYIDIKAN DI KEPOLISIAN DAERAH JAWA BARAT - Anjani, Nur; Mutaqien, Gildan Muslim; Kania, Dede (Lex Jurnalica, 2024)
This article aims to understand how the police, especially the West Java Regional Police, provide protection and handle domestic cases that come to the West Java Regional Police. The research method that the author carried out was an empirical juridical method by looking for data on cases of domestic violence in the West Java Regional Police and assisted by literature studies. The research results show that although many cases have been resolved at the West Java Regional Police, there are also obstacles, one of which is that victims are often reluctant to report domestic violence cases because they are considered a disgrace and only occur within the household. that the victim failed to report and resolve this case to the legal realm. Based on an agreement between the victim and the perpetrator, the resolution of cases that often occurs is with a restorative justice approach, where this justice provides attention to victims who are often ignored even though the justice used is a retributive justice approach which more often has a deterrent effect. the perpetrator and pays little attention to the victim.Keywords:Protection, Police, Household